2018
DOI: 10.7567/jjap.57.080304
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of proton irradiated GaN-based high-power white light-emitting diodes

Abstract: We report the effects of high-energy (23 GeV) proton irradiation at large fluences on packaged high-power GaN-based white light-emitting diodes with YAG:Ce phosphors. From optical and electrical measurements, we assume that proton irradiation degrades only the GaN LED die up to fluences of at least 2 ' 10 14 p/cm 2 , and we demonstrate that it produces nonradiative recombination centres which increase the leakage current and diminish the carrier density in the quantum wells and hence the output optical power. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 38 publications
2
16
0
Order By: Relevance
“…As usual, the Ce 3+ stimulation spectrum has two distinct ranges at ∼330 and 450 nm owing to electron transfer from the base condition of Ce 3+ to another region of crystalline dividing the elements of the stimulated 5d condition of Ce 3+ ( 2 F5/2,7/2 → 5d 1 transformations). 2 In Figure 3, this applies the heated micro-YAG:Ce 3+ , with considerable range among two stimulation ranges. But in the two brand new samples, the bands appeared to considerably widen and lay on each other, which produced a constant wide band between ∼300 and 500 nm.…”
Section: Resultsmentioning
confidence: 99%
“…As usual, the Ce 3+ stimulation spectrum has two distinct ranges at ∼330 and 450 nm owing to electron transfer from the base condition of Ce 3+ to another region of crystalline dividing the elements of the stimulated 5d condition of Ce 3+ ( 2 F5/2,7/2 → 5d 1 transformations). 2 In Figure 3, this applies the heated micro-YAG:Ce 3+ , with considerable range among two stimulation ranges. But in the two brand new samples, the bands appeared to considerably widen and lay on each other, which produced a constant wide band between ∼300 and 500 nm.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, the electric field F in the space-charge region increases with the decrease of voltage. According to (2) and (3), the field-effect functions Γ n , p increase with the electric field F. According to (9), the carrier lifetimes τ n , p decrease with the increase of Γ n , p . In addition, the increase of defects caused by c radiation can reduce carrier lifetime also.…”
Section: International Journal Of Opticsmentioning
confidence: 97%
“…e radiation degradation modes in GaN LEDs have been investigated recently. A variety of radiation studies have been carried out [1][2][3][4][5][6][7], but there are few studies on the effects of c radiation on them [8,9]. Khanna et al [8] found that forward turn-on voltage was increased slightly, the reverse breakdown voltage was unchanged, and the light output intensity was decreased after GaN-based LEDs were radiated by c-rays.…”
Section: Introductionmentioning
confidence: 99%
“…With further development of space technology, GaN-based LEDs as a light source are more and more used in satellites, spacecrafts, accelerator tunnels, missiles, and so on. [102,103] It is important to understand the influence of space radiation on GaN-based space applications. It has been reported that both current-voltage and light output-current characteristics are degraded with increasing the proton dose, and the optical performance of the LEDs is more sensitive to the proton or electron irradiation than that of the corresponding electrical performances.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%